Aktivitas Ekstrak Etanol Daun Alpukat Terhadap Zat Nefrotoksik Ginjal Tikus (ACTIVITIES STUDY OF ETHANOL EXTRACTS OF AVOCADO LEAVES (PERSEA AMERICANA MILL) TO NEPHROTOXIC COMPOUND OF RAT’S KIDNEY) - Wientarsih, Ietje; Harlina, Eva; Purwono, Rini Madyastuti; Utami, Ikrar Trisnaning Hardi (Jurnal Veteriner, 2014)
Based on WHO’s data, about 80% peoples in the word use plant’s extract as herbal medicine. Avocadoleaves has used as herbal medicine which is works as diuretikum, reduce stone in renal, and cure sprue.The purpose of this research is to study activities of ethanol extract of avocado leaves to ethylene glycolinduction on rat’s kidney by histopatologically. This experiment was continuing Adha’s research (2009)with research design as follows: twenty male rats were divided into 4 groups, negative control group (KN),positive control group (KP), treated group I by ethanol extract of avocado leaves 100 mg/kg BW (E100), andtreated group 2 by 300 mg/kg BW (E300). Sampling kidney were fixed in BNF 10% for histopathologicalslide and stained by Hematoxylin-Eosin. The kidney histopathological changes were edema of glomerulus,and protein deposit in the lumen, hyalin droplet and necrotic tubules. The results showed that ethanolextract of avocado leaves can’t significantly to reduce glomerulus edema with percentage cases 31.9% and33.5% for E100 and E300 and tend not to reduce the occurrence of protein deposits in the lumen of thetubule. Ethanol extract of avocado leaves tend to reduce the incidence of tubular necrosis and it wassignificantly different from the KP group (p <0.05). It is caused by flavonoid in etanol extract of avocadoleaves works as diuretikum and antioxidant.
Keywords: avocado leaf, nephrotoxic compound, rat kidney, histopathology